2012
DOI: 10.1108/13683041211204653
|View full text |Cite
|
Sign up to set email alerts
|

Making performance measurement systems more effective in public sector organizations

Abstract: Purpose -Performance management in public sector organizations is a growing phenomenon worldwide. Increasingly, questions are being raised as to its effectiveness in achieving the objective of improving the performance of public sector organizations. Research has shown that there seems to be questionable benefits and many barriers, challenges and problems with implementing performance management and measurement in the public sector environment. The purpose of this paper is to argue that this is due to the lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 30 publications
1
49
0
3
Order By: Relevance
“…In addition, Swanepoel et al (2014) affirm that performance management is an action based on performance measures and reporting, which results in improvement in employee behaviour, motivation and work processes as well as promoting innovation. Performance management is viewed more broadly as a management tool that aims to improve the performance of an organisation (Goh, 2012). Rose (2014) states that recognition refers to a process of acknowledging or giving special attention to a high level of accomplishment or performance, such as customer care or support to colleagues, which is not dependent on achievement against a given target or objective.…”
Section: Work-life Balance As Element Of Total Rewardsmentioning
confidence: 99%
“…In addition, Swanepoel et al (2014) affirm that performance management is an action based on performance measures and reporting, which results in improvement in employee behaviour, motivation and work processes as well as promoting innovation. Performance management is viewed more broadly as a management tool that aims to improve the performance of an organisation (Goh, 2012). Rose (2014) states that recognition refers to a process of acknowledging or giving special attention to a high level of accomplishment or performance, such as customer care or support to colleagues, which is not dependent on achievement against a given target or objective.…”
Section: Work-life Balance As Element Of Total Rewardsmentioning
confidence: 99%
“…According to Goh (2012), for performance management to succeed, employees must believe in the process, the approach, transparent implementation and commitment from managers. Bernthal (1996) also suggested that performance of employees should be managed in a systematic process involving four major stages: planning the process, providing feedback and coaching employees, reviewing or appraising the performance of employees and providing outcomes of the performance reviews or appraisals.…”
Section: Resultsmentioning
confidence: 99%
“…Performance of employees can therefore, be managed in a systematic process involving four major stages: planning the process, providing feedback and coaching employees, reviewing or appraising the performance of employees and providing outcomes of the performance reviews or appraisals (Bernthal, 1996). For performance management to succeed, employees must believe in the process, the approach, transparent implementation and commitment from managers (Goh, 2012). The perception of employees about the performance management processes is therefore important for the success of the process (Sharma, et al, 2016).…”
Section: Performance Managementmentioning
confidence: 99%
“…A avaliação de desempenho é uma ferramenta que pode ser usada para encorajar a melhorar o desempenho das organizações do setor público por meio da definição de objetivos e indicadores de desempenho. A avaliação de desempenho vem tomando espaço na gestão pública com vistas a resolver as questões de responsabilidade e transparência (Goh, 2012).…”
Section: Introductionunclassified